John Dewey's liberalism : individual, community, and self-development - Savage, Daniel M., 1956- (Southern Illinois University Press, 2002)
"John Dewey's classical pragmatism, Daniel M. Savage asserts, can be used to provide a self-development-based justification of liberal democracy that shows the current debate between liberal individualism and republican communitarianism to be based largely on a set of pseudoproblems."--Jacket